2017
DOI: 10.1021/acs.langmuir.6b04094
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Wetting and Spreading of Droplets over Various Substrates

Abstract: There has been a substantial increase in the number of publications in the field of wetting and spreading since 2010. This increase in the rate of publications can be attributed to the broader application of wetting phenomena in new areas. It is impossible to review such a huge number of publications; that is, some topics in the field of wetting and spreading are selected to be discussed below. These topics are as follows: (i) Contact angle hysteresis on smooth homogeneous solid surfaces via disjoining/conjoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 89 publications
0
39
0
Order By: Relevance
“…The pressure inside any droplet (circular axisymmetric shape) differs from the surrounding vapor/air pressure. We believe that, because of the nature of the CB stretching process, the contact angle of the stretched CB quasi-static method corresponds to the static receding contact angle of a droplet, which is closer to the equilibrium contact angle as stated in [23]. Therefore, in this paper the appropriate qualification for the contact angle is static and receding.…”
Section: Contact Angle Measurementsmentioning
confidence: 64%
See 2 more Smart Citations
“…The pressure inside any droplet (circular axisymmetric shape) differs from the surrounding vapor/air pressure. We believe that, because of the nature of the CB stretching process, the contact angle of the stretched CB quasi-static method corresponds to the static receding contact angle of a droplet, which is closer to the equilibrium contact angle as stated in [23]. Therefore, in this paper the appropriate qualification for the contact angle is static and receding.…”
Section: Contact Angle Measurementsmentioning
confidence: 64%
“…The solid/liquid contact angle is a characteristics, related directly to wettability and it is important that it is determined correctly. Issues related to its measurement are discussed in [22,23]. As mentioned in [23], the equilibrium static contact angle of capillary shapes, according to the thermodynamics, contradicts the Laplace equation for the convex surfaces.…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under low slope approximation Jacobi equations for the four unknown functions ( ) are generated, where , = 1, 2 for the system of equations (11) and (12) For a simplified disjoining/conjoining pressure isotherm (see Figure 2), Eqs. (15) and (16) become linear differential equations corresponding to all Jacobi's functions. Initial conditions for four Jacobi's functions [16,32]:…”
Section: Equilibrium Conditions Of Droplets On Deformable Substratesmentioning
confidence: 99%
“…Disjoining/conjoining pressure approach was first introduced by Derjaguin for droplets on solid substrates [12]. More recently it was shown that this approach can also be used for droplets on deformable substrates [11,[13][14][15][16][17]]. 2 of 16 Recently, experimental studies on droplet wetting of deformable substrate have gained a lot of interest primarily due to technological advances in imaging techniques [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%